The Importance of Documentation of the Authenticity of the Copyright of Web-Based Computer Programs (Web-Log Design of Online Motorcycle Taxi Pioneers) as Proof of Legal Ownership - Khalisha Adela Morris; R. Rahaditya (Jurnal Indonesia Sosial Teknologi, 2024)
Web-log design is a work of web-based computer programs that can be protected in terms of coding and display. In the competition of businesses to market their products/services, web-logs are a powerful mainstay to win the competition. With the sophistication of web 3.0 technology, it can make a website a dynamic and attractive digital platform. However, in some cases of copyright infringement, the existence of web applications is still underestimated and even considered only an unprotected concept. The purpose of this study is to analyze illegal acts for alleged copyright infringement of the Online Ojek Pioneer web-log. The research methods used are normative-prescriptive with a legal, case and conceptual approach. Data processing from primary, secondary and tertiary legal sources through literature studies. The analysis was carried out with deductive syllogism. From the results of the study, it can be explained that web-logs are one of the digital works that should be protected. It fulfills the elements of fixed, form, and originality, where the invisible side of the source code is a work of literate work while the appearance is art work. Documentation of the authenticity of each work is important to be prepared early, because it will be a strong evidence when stumbling upon copyright disputes. Suggestions to the DJKI to develop systematic General Data on Creations as a reference for creators to anticipate no copyright infringement and for judges to explore legal findings related to the diversity of computer programs in order to more accurately determine decisions related to the copyright of web-based computer programs.